2019
DOI: 10.1186/s13023-018-0972-6
|View full text |Cite
|
Sign up to set email alerts
|

Achondroplasia: a comprehensive clinical review

Abstract: Achondroplasia is the most common of the skeletal dysplasias that result in marked short stature (dwarfism). Although its clinical and radiologic phenotype has been described for more than 50 years, there is still a great deal to be learned about the medical issues that arise secondary to this diagnosis, the manner in which these are best diagnosed and addressed, and whether preventive strategies can ameliorate the problems that can compromise the health and well being of affected individuals. This review prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
405
3
35

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 350 publications
(458 citation statements)
references
References 349 publications
(514 reference statements)
15
405
3
35
Order By: Relevance
“…Some of the excluded papers provide valuable information on adults with achondroplasia and important aspects of living with a skeletal dysplasia, but did not meet the inclusion criteria for the present scoping review. The most relevant papers are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the excluded papers provide valuable information on adults with achondroplasia and important aspects of living with a skeletal dysplasia, but did not meet the inclusion criteria for the present scoping review. The most relevant papers are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A number of review papers were identified, but were excluded as they were mainly concerning children or because of their non‐systematic methodology . However, we have examined their reference lists for potential eligible original papers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings related to associated anomalies are not readily comparable with other studies that were mainly based on case series. Hydrocephalus in the neonatal period is very rare for infants with achondroplasia, and a later hydrocephalus diagnoses is most likely based either on the presence of benign macrocephaly or equally benign ventriculomegaly (Pauli, ).…”
Section: Discussionmentioning
confidence: 99%